2021
DOI: 10.3390/coatings11030287
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Co-Doped Ga2O3:Si-In Grown by MOCVD

Abstract: We report a highly conductive gallium oxide doped with both silicon and indium grown on c-plane sapphire substrate by MOCVD. From a superlattice structure of indium oxide and gallium oxide doped with silicon, we obtained a highly conductive material with an electron hall mobility up to 150 cm2/V·s with the carrier concentration near 2 × 1017 cm−3. However, if not doped with silicon, both Ga2O3:In and Ga2O3 are highly resistive. Optical and structural characterization techniques such as X-ray, transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…These values are consistent with those reported elsewhere. [16] In summary, the XRD, AFM, and optical characteristics shown earlier revealed quite similar properties for the epitaxial κ-Ga 2 O 3 grown directly on c-sapphire and κ-Ga 2 O 3 grown on β-Ga 2 O 3 buffered c-sapphire, with the exception of the electrical transport. Indeed, the adoption of the β-Ga 2 O 3 template dramatically improved the conductivity and mobility.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…These values are consistent with those reported elsewhere. [16] In summary, the XRD, AFM, and optical characteristics shown earlier revealed quite similar properties for the epitaxial κ-Ga 2 O 3 grown directly on c-sapphire and κ-Ga 2 O 3 grown on β-Ga 2 O 3 buffered c-sapphire, with the exception of the electrical transport. Indeed, the adoption of the β-Ga 2 O 3 template dramatically improved the conductivity and mobility.…”
Section: Resultssupporting
confidence: 66%
“…[19] The κ-Ga 2 O 3 grown directly on c-sapphire was found to be highly/immeasurably resistive (Table 1), as reported previously. [15][16][17] This is most likely due to a relatively poor materials quality and high defect density resulting from the epitaxial strain due to the large lattice mismatch between the c-sapphire and the κ-Ga 2 O 3 epilayer. The κ-Ga 2 O 3 deposited on the β-Ga 2 O 3 buffered c-sapphire, in contrast, showed an electron mobility of 3.5 cm 2 V À1 s À1 with a carrier concentration of around 5.4 Â 10 16 cm À3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the relatively low thermal conductivity of Ga 2 O 3 and the problem of Ga 2 O 3 substrate cost being two orders of magnitude higher than sapphire are both currently hindering the fuller development of Ga 2 O 3 -based powered electronics. In previous studies, we showed that κ-Ga 2 O 3 (an orthorhombic polymorph which is normally considered to be transient) could be stabilized in heteroepitaxial growth on sapphire (0001) substrates by MOCVD [4][5][6][7][8][9][10][11][12]. In this work, we found that high levels of shallow acceptor p-type conduction could be achieved in such layers using silicon impurity doping under Ga rich growth conditions.…”
Section: Introductionmentioning
confidence: 79%
“…The VI/III ratio was either 100 (Ga-rich) or 150 (O-rich). The SiH4 flow rate was fixed at 15 sccm [4][5][6][7][8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%